INCIDENCE OF THERMOPHILIC FUNGI FROM DIFFERENT SUBSTRATES IN ANDHRA PRADESH (INDIA) - RANJITH KUMAR.RAJAVARAM; SREELATHA BATHINI; SIVADEVUNI GIRISHAM; SOLIPURAM MADHUSUDHAN REDDY (International Journal of Pharma and Bio Sciences, 2010)
Total 46 thermophilic fungi were isolated from various substrates such as under ground coalmine soil, bird nest materials, vermicompost, cow dung, poultry litter, decomposing pits, which are prepared with agro waste, municipal waste and zoo dump materials and industrial waste etc. The present paper deals with the isolation of 46 species belonging to 13 genera on different substrates collected from different places of Andhra Pradesh. Among the thermophiles Humicola lanuginosus was present nearly in all substrates and Aspergillus fumigatus found as a thermotolerant in all the substrates.